2008
DOI: 10.1177/0165025407084047
|View full text |Cite
|
Sign up to set email alerts
|

Independence-supportive praise versus interdependence-promoting praise

Abstract: This study used dinnertime observational data to investigate parental praise in Chinese-immigrant and European-American families. Three process models of praise with distinctive communicative content were uncovered. Two models focus on adherence to parental expectations, which promote the development of an interdependent self (interdependence-promoting praise). One focuses on child's self-initiated behaviors and supports the development of an independent self (independence-supportive praise). Consistent with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
(48 reference statements)
3
14
0
Order By: Relevance
“…The findings also are generally consistent with findings reported by Wang et al. (). In their study, Chinese immigrant parents manifested generally high levels of praise for their young children, rates that were similar to U.S. parents generally.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings also are generally consistent with findings reported by Wang et al. (). In their study, Chinese immigrant parents manifested generally high levels of praise for their young children, rates that were similar to U.S. parents generally.…”
Section: Discussionsupporting
confidence: 93%
“…The findings are reminiscent of those reported by Jackson (2012), who also found that Black and Hispanic immigrant mothers were about as likely to get prenatal care and to breastfeed as were their native counterparts. The findings also are generally consistent with findings reported by Wang et al (2008). In their study, Chinese immigrant parents manifested generally high levels of praise for their young children, rates that were similar to U.S. parents generally.…”
Section: Interactions Between Parents and Childrensupporting
confidence: 88%
“…For example, when interacting with their children both American and Japanese mothers tend to simplify their language and use repetitions, but American mothers more frequently name objects than Japanese mothers, who more frequently use objects to encourage social routines and verbal politeness (Fernald & Morikawa, 1993). Similarly, Wang, Wiley, and Chiu (2008) report that European American families tend to praise aspects of behavior that will promote and support independence (e.g., praising self-initiated positive behavior) whereas Chinese immigrant families are more likely to praise aspects of behavior that promote and support interdependence (e.g., praising a child for listening to his/ her parents).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that praise may be used differently in Chinese vs. Euro-Canadian families. For instance, a recent study reported that Chinese parents use praise as a motivator before the desired child behavior (e.g., calmly telling the child that he is a ''good boy'' as a way of communicating the parents' expectations that the child will behave appropriately), whereas EuroNorth American parents typically use praise as a consequence after positive child behavior (e.g., positively telling the child that he is a ''good boy'' for complying to the parents' demands) (Wang et al 2008). Perhaps Chineseimmigrant and Euro-Canadian mothers in this study rated reward techniques as equally acceptable, yet conceptualized rewards differently.…”
Section: Discussionmentioning
confidence: 99%